The Effectiveness of STEM-Based Learning Models on Elementary School Students' Analytical Thinking Skills in Alternative Energy Material - Mudiyatni, Tri; Suryandari, Kartika Chrysti; Musadad, Akhmad Arif (Universitas Sebelas Maret, 2026)
This research is motivated by the problems experienced by students, namely learning emphasizes too much on cognitive abilities, fourth grade students are not yet able to think analytically, and students are not yet able to break down problems into smaller parts. This study aims to analyze the effectiveness of STEM-based learning on alternative energy material for fourth grade elementary school students in Wuryantoro District, and identify changes in their analytical thinking skills after the implementation of the STEM learning model. The research method used is a quantitative experiment with a Quasi-experimental research approach using a pretest and posttest control group design. The observed variables involve the STEM-based learning model with alternative energy material and students' analytical thinking skills. The research sample includes 30 fourth grade students in four elementary schools in Wuryantoro District. The sample was selected using a cluster random sampling technique. Data collection was carried out through observation, tests, and documentation. The results of the study showed that: (1) The STEM-based learning model for the use of alternative energy had a positive impact on fourth-grade students, (2) There were significant changes in students' analytical thinking skills after the application of the STEM-based learning model, and (3) The STEM-based learning model for alternative energy material had significant effectiveness in improving the analytical thinking skills of fourth-grade students. These findings provide an in-depth understanding of the effectiveness of the STEM-based learning model for alternative energy material in developing students' analytical thinking skills.